Teaching English As A Foreign Language: A Portrait Of Primary English Teaching In Kupang - Rahayu, Gupuh - (International Research-Based Education Journal, 2023)
This observational research, which focuses on teacher tactics for teaching English as a Foreign Language to primary school kids, was carried out in two classes at a public primary school. The purpose of this study was to answer the following question: what teaching tactics do the English instructors at this school use? The data were analyzed qualitatively using categories formulated based on theories related to instructional strategies, which include planning and preparing instruction, implementing the teaching and learning process, and assessing students' achievement. The study's primary findings are as follows: 1) Despite the teachers going through the same phases of preparation, the plan is followed and results differ; 2) the teachers can employ games as a learning tool. 3) even though the curriculum demands teachers to integrate the skills (reading, listening, writing, and speaking), in practice, teachers do not teach English in an integrative manner. 4) Time management has become a challenge for teachers at this school. 5) In terms of teacher assessment methodologies, the teachers examine students' success through remedial instruction once a week after the session is ended in areas where students failed to grasp.